2020
DOI: 10.1002/cpp.2506
|View full text |Cite
|
Sign up to set email alerts
|

Meaning‐making as a mediator of anxiety and depression reduction during cognitive behavioral therapy intervention in participants with adjustment disorders

Abstract: There is a consensus among researchers about the link between low meaning in life and anxiety and depressive symptoms. One unanswered question is whether meaning‐making is a mediator of the change in anxiety and depression symptoms in participants with adjustment disorders during cognitive behavioural therapy (CBT) treatment. The aims of this study were (a) to analyse whether there was meaning‐making during the application of the CBT, (b) to analyse whether meaning‐making was a mediator of anxiety psychopathol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 50 publications
3
26
0
Order By: Relevance
“…Frankl states that noogenic depression is characterized by an existential vacuum, absence of meaning in life, boredom, frustration, distress, anxiety, and aggressiveness, and that its etiology would be different from that of endogenous depressions (e.g., neurobiological disturbances, early depressive schemes), indicating that around 20% of depressions are noogenous. Regarding participants with adjustment disorder, several studies have found that meaningmaking was an independent and buffering factor in adjustment in participants with depression and anxiety disorders (e.g., Marco et al, 2020a).…”
Section: Discussionmentioning
confidence: 99%
“…Frankl states that noogenic depression is characterized by an existential vacuum, absence of meaning in life, boredom, frustration, distress, anxiety, and aggressiveness, and that its etiology would be different from that of endogenous depressions (e.g., neurobiological disturbances, early depressive schemes), indicating that around 20% of depressions are noogenous. Regarding participants with adjustment disorder, several studies have found that meaningmaking was an independent and buffering factor in adjustment in participants with depression and anxiety disorders (e.g., Marco et al, 2020a).…”
Section: Discussionmentioning
confidence: 99%
“…That is, people constantly search for and assign meanings to their behaviors, interactions, relationships, objectives and incidents. Thus, subsequent to a stressful event, people begin a set of processes that include searching for and assigning meaning to the event (Marco et al. , 2020).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…These results have important clinical implications. Although previous studies found a strong association between MiL and psychopathology (9,10,14,15), these studies considered (48).…”
Section: Discussionmentioning
confidence: 98%
“…In contrast, people with high comprehension feels that their life is meaningful, that everything happens in a coherent way, and that the positive or negative events that occur daily are integrated into their global schemes. Previous studies found that the meaning-making process moderates and mediates several mental disorders, such as posttraumatic stress disorder (8), eating disorders (9), adjustment disorders (10), and stress (11).…”
Section: Introductionmentioning
confidence: 99%